ПОНЯТТЯ «ІНФОРМАЦІЙНО-ОСВІТНЄ СЕРЕДОВИЩЕ» В АСПЕКТІ ПРОФЕСІЙНОЇ ПІДГОТОВКИ МАЙБУТНІХ ЛОГОПЕДІВ - Цимбал-Слатвінська Світлана (World Science, 2019)
The article clarifies the concept of "information-educational environment" in terms of professional training of speech therapists. The author’s definition of information-educational environment based on the results of the analysis of the concepts "information environment" and "educational environment". It is a synthetic systematic formation accumulating intellectual, cultural, programmatic, organizational and technical resources and involving the use of a wide range of traditional and new information technologies and their technical means aimed to education and development.